Management of the Village-Owned Enterprise (BUMDES) in Paliat Village, Kelua Subdistrict Tabalong Regency - Fakhri Fakhri; Siska Salmawati; Jumai Latte (Journal Research of Social Science, Economics, and Management, 2026)
BUMDes is supported by a solid legal foundation, one of which is (Law Number 6 of 2014) concerning Villages, which aims to accommodate the increase in village income through community economic activities. However, BUMDes Paliat Berkah faces various problems, such as limited business capital still sourced from the personal funds of the administrators, the absence of full-time operational workers, and low support, cooperation, and outreach to the community. This research aims to examine the management of BUMDes Paliat Berkah and identify factors that hinder and support its management. A qualitative approach with a qualitative descriptive type. Data collection techniques were carried out through interviews, observations, and documentation with the determination of informants using purposive of 12 people. The data were reviewed through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the management of BUMDes Paliat Berkah is classified as quite good. The aspects of planning, organization, and control are not optimal, especially related to long-term planning, operational division of labor, and the monitoring system. The aspects of staff placement and motivation are quite good, although still hampered by limited human resources. Inhibiting factors include limited capital, low community participation, and the absence of permanent workers. Supporting factors include the ability of management to anticipate problems in traditional herbal medicine production and the division of tasks according to ability.